“Ratib and Zikir” in Traditional and Modern Dayahs: A Living Qur'an Study in the Southwestern Region of Aceh - Masykar, Tabsyir (TAFSE: Journal of Qur'anic Studies, 2024)
This study explores the implementation and significance of “living Qur'an” practices in traditional and modern dayahs in the Southwestern region of Aceh, aiming to identify these practices, understand their implementation, and investigate the reasons behind their persistence. The research employs a qualitative approach, utilizing case studies and ethnographic observations. The study showed that “living Qur'an” practices, such as Ratib al-Haddad, Ratib al-Attas, Ratib Syahir, and Ratib Lathif in traditional dayahs, and Al-Ma’surat in modern dayahs, are deeply embedded in the dayah culture. These practices are systematically managed and carried out according to set schedules, with reasons including seeking Allah's pleasure, gaining rewards, and preserving scholarly traditions. Both traditional and modern dayahs in the southwestern region of Aceh effectively integrate “living Qur'an” practices into their daily routines, contributing to the spiritual and moral development of their students. These practices, while varied, reflect a commitment to maintaining a strong Islamic identity and adapting to contemporary educational needs.